(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Foodborne infections are a major global concern because of the astoundingly high number of diseases they cause each year. A greater number of highly precise and dependable biosensors have been developed in recent decades to bridge the gap between monitoring requirements and the conventional detection techniques now in use. Among these, aptamer-based biosensors have gained significant attention for their high specificity, stability, and adaptability to diverse targets. Aptamers, single-stranded DNA / RNA molecules with intricate three-dimensional structures, exhibit exceptional molecular recognition capabilities. Their chemical synthesis allows precise sequence design and functional modifications, making them ideal candidates for biosensing applications. Detecting Escherichia coli (E. coli), a common foodborne pathogen is critical for ensuring food safety and public health. While traditional methods such as culture techniques and PCR are reliable, they are often time-consuming and unsuitable for real-time, on-site applications. Aptamer-based biosensors offer rapid, sensitive, and portable alternatives, especially when conjugated with nanomaterials like graphene oxide (GO), gold nanoparticles (AuNPs), and carbon nanotubes. These nanomaterials amplify the signals from aptamer-target interactions through their unique electronic and optical properties, significantly enhancing detection performance. However, achieving optimal functionality necessitates the careful optimization of aptamer nucleotide sequences. Sequence attributes such as length, secondary structure, and nucleotide composition play a crucial role in determining binding affinity, stability, and specificity. Tailored sequence modifications enhance the conjugate’s performance, enabling advanced biosensors with superior accuracy and reliability. This integration of aptamers and nanomaterials demonstrates immense potential in developing low-cost, efficient, and scalable detection systems, addressing the urgent need for effective tools in foodborne pathogen monitoring.